2020
DOI: 10.1111/1471-0528.16339
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐eclampsia‐like syndrome induced by severe COVID‐19: a prospective observational study

Abstract: Objectives To investigate the incidence of clinical, ultrasonographic and biochemical findings related to pre‐eclampsia (PE) in pregnancies with COVID‐19, and to assess their accuracy to differentiate between PE and the PE‐like features associated with COVID‐19. Design A prospective, observational study. Setting Tertiary referral hospital. Participants Singleton pregnancies with COVID‐19 at >20+0 weeks. Methods Forty‐two consecutive pregnancies were recruited and classified into two groups: severe and non‐seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
300
5
45

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(363 citation statements)
references
References 29 publications
13
300
5
45
Order By: Relevance
“…We thank Martin Hirsch and colleagues 1 for their interest in our study 2 and for pointing out a degree of mismatch between our reported findings and the information on the ISRCTN database. The primary outcome of pelvic pain was operationalised more specifically as cyclical pain in the trial, and unfortunately, the secondary outcome of dyspareunia was inadvertently omitted from those listed in the ISRCTN entry.…”
Section: Sirmentioning
confidence: 88%
See 1 more Smart Citation
“…We thank Martin Hirsch and colleagues 1 for their interest in our study 2 and for pointing out a degree of mismatch between our reported findings and the information on the ISRCTN database. The primary outcome of pelvic pain was operationalised more specifically as cyclical pain in the trial, and unfortunately, the secondary outcome of dyspareunia was inadvertently omitted from those listed in the ISRCTN entry.…”
Section: Sirmentioning
confidence: 88%
“…Future trials in endometriosis will now be able to profit from the clear guidance provided by this set of core outcomes, and our understanding of the effective management of this condition will be enhanced accordingly.& Sir, Thank you kindly for the opportunity to respond to the letter from Dr Amorim and her colleagues. 1 We would like to thank Dr Amorim and her team for their interest in our study 2 and their invaluable observations. We acknowledge that our series is small and heterogeneous.…”
Section: Sirmentioning
confidence: 99%
“…One such interesting observation has been made by Mendoza and colleagues who reported PE-like syndrome in six out of eight pregnant patients with severe SARS-CoV-2 pneumonia. 12 However, only one out of six had evidence of placental dysfunction on Doppler examination and biochemical analysis. One more study has reported histopathological changes in placenta from COVID-19 patients postdelivery.…”
Section: Covid-19 and Pe Risk Associationmentioning
confidence: 97%
“…Doppler assessment (uterine artery pulsatility index) and estimation of angiogenic factors (soluble fms-like tyrosine kinase-1/placental growth factor, lactate dehydrogenase) are few of the diagnostic measures to distinguish severe COVID-19 infection from true PE. 12…”
Section: Differentiation Between Severe Covid-19 Infection and Preeclmentioning
confidence: 99%
“…The Doppler assessment (uterine artery pulsatility index) and estimation of angiogenic factors (soluble FMS-like tyrosine kinase-1/placental growth factor and lactate dehydrogenase) are few of the diagnostic measures to distinguish severe COVID-19 infection from true PE. Therefore, diagnosis of preeclampsia 46 in COVID-19 needs a careful approach and should interpreted in all aspects.…”
Section: Covid-19 and Cardioobstetric Risk Indicatorsmentioning
confidence: 99%